"Turn to the East" Policy: Expectations and Reality - Minakir, Pavel Aleksandrovich (Economy of Regions, 2017)
Macroeconomic dynamics, foreign economic relations, reproduction proportions in the Russian economy and the economy of the Russian Far East are analyzed. The author considers sub-global orientation of state economic policy in Russia after 2010. The changing geographic vector of economic policy is analyzed through a modified geographic structure of the expected increase in the country’s export rent, and also through the shift of the center of concentration of resources, which are necessary to form a new pole of growth in the national economy. The author reviews macroeconomic dynamics and analyzes the factors of the cyclical development of the Russian economy. The paper evaluates the dynamics of the geographical structure of foreign markets. The author’s hypothesis suggests that foreign trade interactions are not sufficiently restructured to reconceive economic policies. For this purpose, the institutional integration within the new integration space is of critical importance. The article considers trends and regularities that explain the equilibrium parameters of the economic system of the Russian Far East, as well as the possibility of transition to new equilibrium levels. The author discusses the ratio of investment and institutional factors of modernization and the formation of stable positive macroeconomic and structural dynamics in the region. Based on Russian and foreign scientific literature, I consider the most common interpretations of threats and opportunities for the economic development of the Russian Far East, including the impact of demographic trends, structural improvement, competitive environment factors, institutional innovations. The study discusses the influence of the Chinese «one belt — one way» project on the prospects for implementing the domestic and foreign eastern economic policy of the Russian Federation.